2020
DOI: 10.1038/s41541-020-00219-x
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant formulated virus-like particles expressing native-like forms of the Lassa virus envelope surface glycoprotein are immunogenic and induce antibodies with broadly neutralizing activity

Abstract: Lassa mammarenavirus (LASV) is a rodent-borne arenavirus endemic to several West African countries. It is the causative agent of human Lassa fever, an acute viral hemorrhagic fever disease. To date, no therapeutics or vaccines against LASV have obtained regulatory approval. Polyclonal neutralizing antibodies derived from hyperimmunized animals may offer a useful strategy for prophylactic and therapeutic intervention to combat human LASV infections. The LASV envelope surface glycoprotein complex (GP) is the maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 84 publications
3
23
0
1
Order By: Relevance
“…In a recent study, adjuvanted virus-like particles expressing a stable native-like LASV Josiah GP trimer induced the production of hyperimmune sera in rabbits with the capacity to neutralize multiple strains of LASV in vitro. It has yet to be determined if this system can induce sufficiently high titers of neutralizing antibodies to protect against LASV challenge in animal models 67 . Meanwhile, another study has suggested that non-neutralizing antibodies may play a role in controlling infection through antibody-dependent cellular phagocytosis or antibody-dependent cellular cytotoxicity 29 .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, adjuvanted virus-like particles expressing a stable native-like LASV Josiah GP trimer induced the production of hyperimmune sera in rabbits with the capacity to neutralize multiple strains of LASV in vitro. It has yet to be determined if this system can induce sufficiently high titers of neutralizing antibodies to protect against LASV challenge in animal models 67 . Meanwhile, another study has suggested that non-neutralizing antibodies may play a role in controlling infection through antibody-dependent cellular phagocytosis or antibody-dependent cellular cytotoxicity 29 .…”
Section: Discussionmentioning
confidence: 99%
“…).DENV-LPs/1CprME, /1prME, /4CprME, and /4prME could generate IgG antibody levels since many VLPs include structural or molecular characteristics that give certain auto-immunostimulatory qualities. These features enable VLPs to induce immunological responses without the use of adjuvants; nevertheless, adjuvants may enhance vaccination immunogenicity and encourage the activation of a speci c type of immune response when combined with VLP vaccines(Cimica and Galarza 2017;Donaldson et al 2018;Müller et al 2020). Our ITC data indicate that DENV-LP/1CPrME and DENV-LPs/4CPrME have a lower K D and ΔG than DENV-LP/1prME and DENV-LPs/4prME.…”
mentioning
confidence: 81%
“…Lass mammarenavirus-like protein nanoparticles were studied for the intramuscular delivery of the glycoprotein of Lassa mammarenavirus [46]. Lassa mammarenavirus is a rodent arenavirus that can cause acute hemorrhagic fever disease in humans [47].…”
Section: Protein-based Nanomaterials For the Delivery Of Protein Viramentioning
confidence: 99%
“…The combination of nanovaccines with other adjuvant systems needs to be studied further. A few studies reported that enhanced immunogenicity was achieved by combining nanovaccines with commercial adjuvants [46], or codelivering nanovaccines with adjuvants in a nanomaterial. In cancer immunotherapy, the entrapment of various immune adjuvants (e.g., imiquimod) was found to enhance dendritic cells maturation and systemic immune responses [86].…”
Section: Challenges and Perspectivesmentioning
confidence: 99%